GWO-based MPPT controller for grid connected Solid oxide fuel cell with high step up DC-DC converter - Sudhakiran Ponnuru; R. Ashok Kumar; N. M. Jothi Swaroopan (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The solid oxide fuel cell (SOFC) is used as secondary source in micro grid application. When the renewable sources are not able meet the load requirement, Battery energy back-up system is supposed to supply the energy to meet the demand. The SOFC come into action when the state of charge (SOC) of battery energy backup becomes too low. The SOFC parameters are assumed as constant during its operation but those operating parameters are not practically constant. The operating parameters vary widely which will influence the output voltage of SOFC. Hence an optimum power extracting controller is being implemented to ensure maximum power under dynamic operating condition. A high step up converter is designed to boost the output voltage of SOFC whose steady state analysis is studied in this work. The switches of high step up converter are triggered using optimum power controller using grey wolf based optimization algorithm. The proposed controller performance is compared with conventional particle swarm optimization based controller. The simulation is carried out using MATLAB/simulink and results discussed.